2006
DOI: 10.1103/physrevlett.96.253002
|View full text |Cite
|
Sign up to set email alerts
|

g-Factor of Heavy Ions: A New Access to the Fine Structure Constant

Abstract: A possibility for a determination of the fine structure constant in experiments on the bound-electron g-factor is examined. It is found that studying a specific difference of the g-factors of B- and H-like ions of the same spinless isotope in the Pb region to the currently accessible experimental accuracy of 7 x 10(-10) would lead to a determination of the fine structure constant to an accuracy which is better than that of the currently accepted value. Further improvements of the experimental and theoretical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
127
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(131 citation statements)
references
References 29 publications
0
127
0
4
Order By: Relevance
“…In Ref. 7 it was shown that both the parameter ξ and the difference g ′ are very stable with respect to variations of the nuclear structure parameters. At the same time the α-dependent term is reduced in this difference by about 4% only.…”
Section: Determination Of the Fine Structure Constantmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. 7 it was shown that both the parameter ξ and the difference g ′ are very stable with respect to variations of the nuclear structure parameters. At the same time the α-dependent term is reduced in this difference by about 4% only.…”
Section: Determination Of the Fine Structure Constantmentioning
confidence: 99%
“…As was shown in Refs. 6,7 , this can be done by studying specific differences of the g factors of H-, Li-, and B-like ions. Therefore, accurate calculations of all these ions are required to provide stringent tests of the theoretical methods employed for the g-factor calculations and to use these studies for determination of the fundamental constants.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [40] it was shown that the ultimate accuracy limit can be significantly reduced in the difference…”
Section: Bound-electron G-factormentioning
confidence: 99%
“…This independent scheme may be used to extract the fine-structure constant from a comparison of experimental and theoretical bound-electron g-factors with an accuracy competitive with or better than the current value. 0.000 000 601 506 0 α(Zα) 4 0.000 000 014 797 0 α(Zα) 5+ 0.000 000 015 48 (52) 2-loop QED α 2 (Zα) 0 −0.000 003 186 116 6 α 2 (Zα) 2 −0.000 000 000 917 9 α 2 (Zα) 4 −0.000 000 000 084 4 α 2 (Zα) 5+ 0.000 000 000 00 (13) ≥ 3-loop QED α 3 (Zα) 0 0.000 000 026 517 7 (1) α 3 (Zα) 2 0.000 000 000 007 6 α 3 (Zα) 4+ 0.000 000 000 000 0 (11) Recoil:…”
mentioning
confidence: 99%
“…In Ref. [4] (see also [5]), a specific weighted difference of the g-factors of heavy H-and B-like ions with the same Z was put forward. It was demonstrated that the theoretical uncertainty of the nuclear size effect in this difference can be brought down to 4 × 10 −10 for heavy ions around Pb, which was several times smaller than the uncertainty due to α at that time.…”
mentioning
confidence: 99%